UPS and XPS study of annealed and unannealed poly-3-hexyl-thiophene. - Kwan, Yue Chau. (2011)
Ultraviolet Photoelectron Spectrometry (UPS) and X-ray Photoelectron Spectrometry (XPS) allow for different techniques in detecting resonance in carbon based compounds. Using amorphous carbon and graphite as reference samples, it is shown that resonance results in a widening of a characteristic peak in the spectra, an increase in the number of electrons in the region of low binding energy (3.0eV - 9.0eV), a reduction in the energy gap between the valence band edge and the Fermi level and a reduction in the valence band edge to the vacuum level; visible under a UPS measurement. A XPS measurement reveals a shake-up feature that can be used to determine the dominant band to band transition in the material. Using these results, annealed and unannealed Poly-3-Hexyl-Thiophene (P3HT) can characterized and compared. Annealed P3HT exhibits a larger number of electrons in the region of low binding energy electrons, a lower ionization energy but no change in the Valence band edge - Fermi level gap when compared against unannealed P3HT. XPS measurements reveal a dominant π → π∗ transition 6.0eV away from the main C1s peak without any associated C1s peak widening.